Acid-Catalyzed Oxidative Addition of Thiols to Olefins and Alkynes for a One-Pot Entry to Sulfoxides - Yue, Hui-Lan; Klussmann, Martin (Synlett, 2016)
An oxidative variant of the thiol-ene reaction has been developed, achieving the direct addition of thiols to olefins to form sulfoxides. The reaction uses tert-butyl hydroperoxide as oxidant and methanesulfonic acid as catalyst. The latter is believed to catalyze the oxidation of the intermediate sulfide to the sulfoxide. No special precautions are necessary to exclude oxygen, yet the products are formed without oxidation at the β-position. Styrenes, acrylic acid derivatives, alkynes, and thiophenols gave the highest yields, while aliphatic olefins and thiols were less effective.
Keywords: addition; homogeneous catalysis; oxygenations; peroxides; radical reaction; sulfoxides